Aspirin-triggered lipoxin A4 blocks reactive oxygen species generation in endothelial cells: A novel antioxidative mechanism - Nascimento-Silva, Vany; Arruda, Maria Augusta; Barja-Fidalgo, Christina; Fierro, Iolanda M. (Thrombosis and Haemostasis, 2007)
Lipoxins and their aspirin-triggered carbon-15 epimers have emerged as mediators of key events in endogenous anti-inflammation and resolution. However, the implication of these novel lipid mediators on cardiovascular diseases such as hypertension, atherosclerosis, and heart failure has not been investigated. One of the major features shared by these pathological conditions is the increased production of reactive oxygen species (ROS) generated by vascular NAD(P)H oxidase activation. In this study, we have examined whether an aspirin-triggered lipoxin A4 analog (ATL-1) modulates ROS generation in endothelial cells (EC). Pre-treatment of EC with ATL-1 (1–100 nM) completely blocked ROS production triggered by different agents, as assessed by dihydrorhodamine 123 and hydroethidine. Furthermore, ATL-1 inhibited the phosphorylation and translocation of the cytosplamic NAD(P)H oxidase subunit p47phox to the cell membrane as well as NAD(P)H oxidase activity. Western blot and immunofluorescence microscopy analyses showed that ATL-1 (100 nM) impaired the redox-sensitive activation of the transcriptional factor NF-κB, a critical step in several events associated to vascular pathologies. These results demonstrate that ATL-1 suppresses NAD(P)H oxidase-mediated ROS generation in EC, strongly indicating that lipoxins may play a protective role against the development and progression of cardiovascular diseases.
Keywords: ATL; lipoxin; NAD(P)H oxidase; angiotensin; cardiovascular disease